(untitled) (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2015)
The physicochemical parameters (refractive index, water content, β-carotene, color parameters and content of glucose, fructose, sucrose and oligosaccharides for 14 types of bee honey have been investigated. They are grouping according to the following parameters:• Geographic region 1 – valley-mountain • Geographic region2 – North or South Bulgaria • Year of producing – 2008 or 2009 • Botanical origin – honeydew, multiflorous, sunflower, lime. Analysis of the data gives the opportunity for characterizing the samples of bee honey by using discriminant analysis. The models correctly present geographic region, year of producing, botanical origin and it can be used for determining the type of unidentified samples.